Analysis of Impedance Source Inverter Topologies for Grid integration of PV inverters - Arasakumar Sangari; R Umamaheswari (Institute of Advanced Engineering and Science, 2015)
In this paper, the performance of different Impedance Source Inverter (ZSI) topologies in implementing single stage power conversion for grid ingetertion of PV power converters is discussed.Unlike the traditional inverters, ZSI employs a distinctive impedance network, thereby making shoot-through state is possible. The independent control variables are shoot-through duty ratio and modulation index. Simple Boost Control pulse width modulation technique was used in this work to vary the modulation index. Here the basic operation, simple boost control method, characteristics, requirements and harmonic analysis of the classical Z-Source Inverter (ZSI), TZ-Source Inverter (TZSI), Trans-Z-Source Inverter (Trans-ZSI) and Improved ZSI (IMZSI) topologies were compared for interfacing the wide range variable input energy to utility supply system. The performances were compared based on its MATLAB/SIMULINK simulation model and featured results are shown to confirm its validity.